PENGESAHAN PERJANJIAN PERKAWINAN PASCA PUTUSAN MAHKAMAH KONSTITUSI - Amalia, Berlianny; Erliyani, Rahmida (Collegium Studiosum Journal, 2024)
Constitutional Court Decision No. 69/PUU-XIII/2015 provides new legal politics, namely that a marriage agreement can be made after marriage. The verdict gives certainty and responsibility to marriage registration officers or notaries to ratify collective agreements, namely marriage agreements after the marriage is held. This research examines the regulation of the ratification of marriage agreements after the issuance of Constitutional Court Decision No. 69/PUU-XIII/2015; as well as the implications of Constitutional Court Decision No. 69/PUU-XIII/2015 on the authority of notaries in the ratification of marriage agreements. The type of research used is normative, with a statutory approach and a conceptual approach. Prior to Constitutional Court Decision No. 69/PUU-XXI/2015, marital agreements were regulated in Law No. 1 Year 1974, where marital agreements could only be made before the marriage took place. After the birth of Constitutional Court Decision No. 69/PUU-XII/2015, a marriage agreement can not only be made before marriage but can also be made after marriage. The ratification of the marriage agreement can not only be done by the marriage registration officer, but also by a notary. So that with the Constitutional Court Decision No. 69/PUU-XII/2015, it adds to the authority of notaries to ratify marriage agreements. The ratification of a marriage agreement by a notary is carried out by pouring the contents of the agreement between husband and wife into an authentic deed. Then the parties are obliged to register it at the local Civil Registry Office to obtain a marriage contract.